Method for preparing submicron-sized uniform-sphere-shaped silica by synergic hydrolysis of silicic acid ester
Patent Information
- Application Number
- CN202611217088.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0009](1)粒径分布较宽,难以获得高均一性颗粒;
[0043](1)粒径分布窄
Smart Images

Figure CN122977392A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic powder material preparation technology, and in particular to a method for preparing submicron-sized uniform spherical silica by synergistic hydrolysis of silicate esters. Background Technology
[0002] Spherical silica materials are widely used in electronic packaging, semiconductor CMP polishing, precision ceramics, optical materials, catalyst supports, coating fillers, and functional composite materials due to their high chemical stability, low dielectric constant, high specific surface area, excellent flowability, and good thermal stability. Among them, submicron-sized uniform spherical silica has significant application value in high-end electronic packaging and advanced functional materials due to its uniform particle size, high packing density, and few interface defects.
[0003] Currently, the mainstream methods for preparing spherical silica mainly include the gas-phase method, precipitation method, microemulsion method, and alkoxide hydrolysis method. Among them, the gas-phase method, although producing high purity, suffers from problems such as large equipment investment, high energy consumption, and difficulty in particle size control; the particles prepared by the precipitation method usually have a wide particle size distribution and poor sphericity; although the microemulsion method can obtain more uniform particles, the system is complex, surfactants are difficult to completely remove, and the industrialization cost is high.
[0004] In contrast, the Stöber method, using silicate esters as precursors, has become an important technical route for preparing monodisperse spherical silica due to its simple process, mild reaction conditions, easily controllable particle size, and good reproducibility. This method typically uses tetraethoxysilane (TEOS) as the silicon source, undergoing hydrolysis and condensation reactions in an ethanol-water-ammonia system to form spherical SiO2 particles. Studies have shown that factors such as ammonia concentration, water content, silicon source concentration, and dropping method significantly affect the nucleation rate and final particle size distribution.
[0005] In the existing technology, there is already a considerable amount of research on the preparation of silica microspheres using the Stöber method. For example, the patent document "A process for preparing silica microspheres based on the Stöber method" discloses a method for preparing silica microspheres using the Stöber method, and focuses on optimizing the drying and grinding processes. However, its core still uses a single silicon source system and does not further control the particle size uniformity during the nucleation process. Therefore, at the submicron scale, it is still prone to problems such as widening of particle size distribution and particle agglomeration.
[0006] Furthermore, some existing technologies increase particle size by increasing ammonia or TEOS concentrations. However, under high concentration conditions, the local hydrolysis rate of the system accelerates significantly, easily leading to secondary nucleation and uneven particle distribution. Related studies have shown that while particles can grow rapidly when TEOS and ammonia concentrations increase, the system is more prone to hard agglomeration and non-spherical particles.
[0007] Other studies employ electrolyte regulation, two-phase interface reactions, or continuous flow processes to improve particle uniformity. For example, continuous flow silicon sphere preparation technology improves particle size distribution by controlling the feeding method, but it requires high precision in continuous equipment conveying, resulting in high industrial implementation costs. While the two-phase interface method can reduce particle polydispersity, system control is complex, pH window requirements are strict, and process stability remains limited.
[0008] Furthermore, most existing methods use a single TEOS as the silicon source. Because TEOS hydrolyzes rapidly in alkaline systems, it easily forms high concentrations of silanol intermediates in localized areas, leading to localized supersaturation, particle collision and aggregation, and secondary nucleation problems. This issue is particularly pronounced in submicron-scale high-solids-content systems. Ultimately, this results in the following defects in the obtained silica particles:
[0009] (1) The particle size distribution is relatively wide, making it difficult to obtain highly uniform particles;
[0010] (2) Insufficient sphericity, with elliptical or irregular particles present;
[0011] (3) The particles have a high hydroxyl density on their surface, making them prone to irreversible agglomeration after drying;
[0012] (4) The stability of the system decreases when the yield is increased, which is not conducive to continuous industrial scale-up;
[0013] (5) Existing processes are sensitive to the reaction window and have poor batch stability.
[0014] In recent years, some studies have attempted to introduce organosilicone esters such as methyltriethoxysilane (MTES) as co-silicon sources to regulate the formation rate of silicon-oxygen networks. The organic groups in organosilicone esters can reduce the local condensation rate and improve the steric hindrance effect on the particle surface, thereby improving particle uniformity and anti-agglomeration performance to a certain extent.
[0015] However, current research on composite silicate synergistic hydrolysis systems mainly focuses on mesoporous materials or surface modification, lacking systematic research on the precise nucleation control, synergistic hydrolysis kinetic regulation, and industrial-scale stable preparation of submicron-sized uniform spherical silica particles. In particular, there is still significant room for improvement in controlling the particle size distribution index (PDI), reducing hard agglomeration, and improving sphericity.
[0016] Therefore, developing a method for preparing spherical silica based on a synergistic hydrolysis mechanism of composite silicates that can achieve submicron-level uniform particle size, high sphericity, low agglomeration, and is suitable for industrial scale-up has significant engineering application value and industrialization significance. Summary of the Invention
[0017] Based on the problems raised in the background technology mentioned above, this invention proposes a method for the synergistic hydrolysis preparation of submicron-sized uniform spherical silica from silicates.
[0018] The technical solution is as follows:
[0019] A method for preparing submicron-sized uniform spherical silica by synergistic hydrolysis of silicate esters includes the following steps:
[0020] (1) Preparation of alkaline alcohol-water reaction system:
[0021] According to the mass fraction, 65-78 parts of anhydrous ethanol, 12-20 parts of deionized water and 4-8 parts of ammonia water are added to the reactor and stirred at 400-700 rpm for 10-25 minutes at 20-30℃ to form a homogeneous alkaline alcohol-water system.
[0022] (2) Preparation of composite silicate precursor solution:
[0023] According to the mass fraction, 18-28 parts of tetraethoxysilane and 1.5-4.5 parts of methyltriethoxysilane are mixed, and then 0.2-1.2 parts of dispersant stabilizer are added. The mixture is stirred at room temperature for 5-20 minutes to obtain a composite silicate precursor solution.
[0024] (3) Synergistic hydrolysis and condensation reaction:
[0025] The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a rate of 0.8–3.0 mL / min. During the dropwise addition, the reaction temperature is controlled at 25–35 °C and the stirring speed is controlled at 500–900 rpm. After the dropwise addition is completed, the reaction continues for 3–8 h to allow the silicate to undergo synergistic hydrolysis and condensation reaction to generate submicron-sized spherical silica slurry.
[0026] (4) Solid-liquid separation and washing:
[0027] The obtained slurry was centrifuged at 5000-9000 rpm for 5-15 min, the precipitate was collected, and washed 2-4 times alternately with anhydrous ethanol and deionized water, with the amount of washing solution added each time being 4-8 times the mass of the precipitate.
[0028] (5) Drying treatment:
[0029] The washed product was dried under vacuum at 50–80°C for 6–12 hours to obtain submicron-sized uniform spherical silica powder.
[0030] As a preferred embodiment of the present invention, the anhydrous ethanol has a purity ≥ 99.5 wt.% and the deionized water has a conductivity ≤ 1 μS / cm.
[0031] As a preferred embodiment of the present invention, the ammonia concentration is 25-28 wt.%.
[0032] As a preferred embodiment of the present invention, the tetraethoxysilane has a purity ≥99wt.% and its chemical formula is Si(OC2H5)4; the methyltriethoxysilane has a purity ≥98wt.% and its chemical formula is CH3Si(OC2H5)3.
[0033] As a preferred embodiment of the present invention, the dispersion stabilizer is prepared by dissolving polyethylene glycol dicarboxylic acid in anhydrous toluene, adding p-toluenesulfonic acid to construct an anhydrous homogeneous system, and then preparing the stabilizer through a three-step process, the specific preparation steps of which are as follows:
[0034] According to the mass ratio: weigh 10-20 parts of polyethylene glycol dicarboxylic acid, 2-6 parts of 1-(3-hydroxypropyl)pyrrole, 0.3-2 parts of guaiacol, 3-6 parts of p-toluenesulfonic acid, and 200-300 parts of anhydrous toluene;
[0035] Step 1, Low-temperature esterification: 1-(3-hydroxypropyl)pyrrole is added at 75-80℃ and selectively esterified with the carboxyl group at one end of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate;
[0036] Step 2, high-temperature esterification: The temperature is raised to 90-100℃ and guaiacol is added to complete the double-end grafting with the remaining carboxyl groups; at this temperature, toluene and water azeotropically carry out the reaction water, promoting the complete esterification.
[0037] The third step is purification: the reaction ends when the acid value of the system is constant and no water is precipitated. After neutralization and impurity removal, desolventization under reduced pressure and vacuum drying, a double-end grafted modified composite esterification stabilizer is obtained.
[0038] As a preferred technical solution of the present invention, the material is added in step (3) by constant rate dripping, and the dripping time is controlled to be 40 to 180 min.
[0039] As a preferred technical solution of the present invention, the synergistic hydrolysis reaction in step (3) is carried out in a closed reactor at a pressure of atmospheric pressure to 0.08 MPa.
[0040] As a preferred embodiment of the present invention, the total solid content of the reaction system in step (3) is controlled to be 6-14 wt.%.
[0041] Reaction Mechanism: This invention uses tetraethoxysilane and methyltriethoxysilane as composite silicate monomers to achieve synergistic hydrolytic condensation in an alcohol-water alkaline system. Simultaneously, a composite stabilizer prepared by stepwise esterification of ethylene glycol dicarboxylic acid, 1-(3-hydroxypropyl)pyrrole, and guaiacol is introduced, and a sterically hindered interface is constructed through double-end grafting modification. The composite silicon source can moderate the formation rate of silanol intermediates, avoiding local supersaturation and secondary nucleation, enabling synchronous nucleation and uniform anisotropic growth of particles. The modified stabilizer adsorbs onto the particle surface, inhibiting interparticle hydrogen bonding and collisional aggregation, regulating sol-gel condensation kinetics, and ultimately forming submicron-sized spherical silica particles with regular morphology, uniform particle size, and low agglomeration.
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] (1) Narrow particle size distribution
[0044] By employing synergistic hydrolysis of dual silicates, the silanol formation rate becomes more gradual, reducing local supersaturation and enabling synchronous nucleation of particles. The resulting product's PDI can be controlled below 0.08.
[0045] (2) High sphericity
[0046] By adjusting the participation of organosilicone esters in the polycondensation reaction, the local crosslinking rate on the particle surface is reduced, allowing the particles to grow uniformly in all directions, thereby obtaining particles with high sphericity.
[0047] (3) Excellent anti-agglomeration performance
[0048] The organic groups in organosilicone esters can form steric hindrance on the particle surface, reduce interparticle hydrogen bonding, and significantly reduce hard agglomeration during the drying process.
[0049] (4) High process stability
[0050] This invention does not require complex template agents or emulsion systems; it can achieve precise particle size control simply by regulating the composite silicon source. The process is simple and has good repeatability.
[0051] (5) Suitable for industrial scale-up
[0052] The entire reaction system is an atmospheric pressure liquid phase system, the reaction is mild, and it is suitable for continuous and large-scale production. Attached Figure Description
[0053] Figure 1 Electron micrograph of the spherical silica prepared in Example 1;
[0054] Figure 2 The infrared spectrum of the spherical silica prepared in Example 1 shows that it is completely hydrolyzed, has a dense network, and has a suitable amount of hydroxyl groups and adsorbed water on the surface.
[0055] Figure 3 The XRD pattern of the spherical silica prepared in Example 1 shows a broadened peak at ~22°, confirming that it is a pure amorphous state. Detailed Implementation
[0056] The preferred embodiments of the present invention will now be described. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0057] Example 1
[0058] (1) Preparation of alkaline alcohol-water reaction system: 65 kg of anhydrous ethanol, 12 kg of deionized water and 4 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 25 wt.%; the mixture was stirred at 400 rpm for 10 min at 20℃ to form a clear and homogeneous alkaline alcohol-water system.
[0059] (2) Preparation of composite silicate precursor solution: According to the mass kg, 18 kg of tetraethoxysilane and 1.5 kg of methyltriethoxysilane are mixed. The purity of tetraethoxysilane is ≥99 wt.% and the purity of methyltriethoxysilane is ≥98 wt.%. Then add 0.2 kg of dispersant stabilizer, stir at room temperature for 5 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0060] The specific preparation process of the dispersion stabilizer is as follows: Weigh 10 kg of polyethylene glycol dicarboxylic acid, 2 kg of 1-(3-hydroxypropyl)pyrrole, 0.3 kg of guaiacol, 3 kg of p-toluenesulfonic acid, and 200 kg of anhydrous toluene according to the mass ratio (kg); Step 1, low-temperature esterification: Add 1-(3-hydroxypropyl)pyrrole at 75℃ and selectively esterify it with the carboxyl group at one end of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate; Step 2, high-temperature esterification: Raise the temperature to 90℃ and add guaiacol to esterify it with the remaining carboxyl group to complete the double-end grafting; at this temperature, toluene and water azeotropically react to continuously remove the reaction water, promoting complete esterification; Step 3, purification treatment: With the system acid value constant and no water precipitation as the reaction endpoint, neutralize and remove impurities, desolventize under reduced pressure, and vacuum dry to obtain a double-end grafted modified composite esterification stabilizer.
[0061] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a constant rate of 0.8 mL / min. The reaction is carried out in a closed reactor at atmospheric pressure. The total dropwise time is controlled at 40 min. The reaction temperature is controlled at 25 °C and the stirring speed is controlled at 500 rpm during the dropwise process. After the dropwise addition is completed, the reaction is continued at a constant temperature for 3 h. The total solid content of the reaction system is controlled at 6 wt.% throughout the process. The two silicates undergo synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0062] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 5000 rpm for 5 min and the bottom solid precipitate was collected. It was washed twice with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 4 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0063] (5) Drying treatment: The washed wet product is placed in a vacuum drying oven at 50°C and dried under vacuum for 6 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0064] Example 2
[0065] (1) Preparation of alkaline alcohol-water reaction system: 71.5 kg of anhydrous ethanol, 16 kg of deionized water and 6 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 26.5 wt.%; the mixture was stirred at 550 rpm for 17.5 min at 25℃ to form a clear and homogeneous alkaline alcohol-water system.
[0066] (2) Preparation of composite silicate precursor solution: According to mass kg, 23 kg of tetraethoxysilane and 3.0 kg of methyltriethoxysilane are mixed, with the purity of tetraethoxysilane ≥99 wt.% and the purity of methyltriethoxysilane ≥98 wt.%; then add 0.7 kg of dispersant stabilizer, stir at room temperature for 12.5 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0067] The specific preparation process of the dispersion stabilizer is as follows: Weigh 15 kg of polyethylene glycol dicarboxylic acid, 4 kg of 1-(3-hydroxypropyl)pyrrole, 1.15 kg of guaiacol, 4.5 kg of p-toluenesulfonic acid, and 250 kg of anhydrous toluene according to the mass ratio (kg); Step 1, low-temperature esterification: Add 1-(3-hydroxypropyl)pyrrole at 77.5℃ and selectively esterify it with the carboxyl group at one end of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate; Step 2, high-temperature esterification: Raise the temperature to 95℃ and add guaiacol to esterify it with the remaining carboxyl group to complete the double-end grafting; at this temperature, toluene and water azeotropically react to continuously remove the reaction water, promoting complete esterification; Step 3, purification treatment: With the system acid value constant and no water precipitation as the reaction endpoint, neutralize and remove impurities, desolventize under reduced pressure, and vacuum dry to obtain the double-end grafted modified composite esterification stabilizer.
[0068] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution was added dropwise to the alkaline alcohol-water system at a constant rate of 1.9 mL / min. The reaction was carried out in a closed reactor with a reaction pressure of 0.04 MPa. The total dropwise time was controlled to be 110 min. The reaction temperature was controlled to be 30 °C and the stirring speed was 700 rpm during the dropwise process. After the dropwise addition was completed, the reaction was continued at a constant temperature for 5.5 h. The total solid content of the reaction system was controlled to be 10 wt.% throughout the process. The two silicates underwent synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0069] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 7000 rpm for 10 min and the bottom solid precipitate was collected. It was washed three times with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 6 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0070] (5) Drying treatment: The washed wet product is placed in a vacuum drying oven at 65℃ and dried under vacuum for 9 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0071] Example 3
[0072] (1) Preparation of alkaline alcohol-water reaction system: 75 kg of anhydrous ethanol, 18 kg of deionized water and 7 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 27.2 wt.%; the mixture was stirred at 620 rpm for 22 min at 28℃ to form a clear and homogeneous alkaline alcohol-water system.
[0073] (2) Preparation of composite silicate precursor solution: According to mass kg, 26 kg of tetraethoxysilane and 3.8 kg of methyltriethoxysilane are mixed, with the purity of tetraethoxysilane ≥99 wt.% and the purity of methyltriethoxysilane ≥98 wt.%; then add 1.0 kg of dispersant stabilizer, stir at room temperature for 16 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0074] The specific preparation process of the dispersion stabilizer is as follows: 18 kg of polyethylene glycol dicarboxylic acid, 5 kg of 1-(3-hydroxypropyl)pyrrole, 1.6 kg of guaiacol, 5.2 kg of p-toluenesulfonic acid, and 280 kg of anhydrous toluene are weighed according to the mass ratio (kg). Step 1: Low-temperature esterification: 1-(3-hydroxypropyl)pyrrole is added at 79℃ and selectively esterified with one end of the carboxyl group of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate. Step 2: High-temperature esterification: Guaifenesin is added at 98℃ and esterified with the remaining carboxyl group to complete the double-end grafting. At this temperature, toluene and water azeotropically react to continuously remove reactive water, promoting complete esterification. Step 3: Purification: The reaction endpoint is defined as a constant acid value and no reactive water precipitation. After neutralization, impurity removal, desolventization under reduced pressure, and vacuum drying, a double-end grafted modified composite esterification stabilizer is obtained.
[0075] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution was added dropwise to the alkaline alcohol-water system at a constant rate of 2.4 mL / min. The reaction was carried out in a closed reactor with a reaction pressure of 0.06 MPa. The total dropwise time was controlled to be 150 min. The reaction temperature was controlled to be 33 °C and the stirring speed was 800 rpm during the dropwise process. After the dropwise addition was completed, the reaction was continued at a constant temperature for 7 h. The total solid content of the reaction system was controlled to be 12 wt.% throughout the process. The two silicates underwent synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0076] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 8000 rpm for 12 min and the bottom solid precipitate was collected. It was washed three times with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 7 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0077] (5) Drying treatment: The washed wet product was placed in a vacuum drying oven at 72℃ and dried under vacuum for 10.5h to completely remove residual solvent and moisture, and finally obtained submicron-sized uniform spherical silica powder.
[0078] Example 4
[0079] (1) Preparation of alkaline alcohol-water reaction system: 78 kg of anhydrous ethanol, 20 kg of deionized water and 8 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 28 wt.%; the mixture was stirred at 700 rpm for 25 min at 30℃ to form a clear and homogeneous alkaline alcohol-water system.
[0080] (2) Preparation of composite silicate precursor solution: According to the mass kg, 28 kg of tetraethoxysilane and 4.5 kg of methyltriethoxysilane are mixed. The purity of tetraethoxysilane is ≥99 wt.% and the purity of methyltriethoxysilane is ≥98 wt.%. Then add 1.2 kg of dispersant stabilizer and stir at room temperature for 20 min. After mixing evenly, a clear composite silicate precursor solution is obtained.
[0081] The specific preparation process of the dispersion stabilizer is as follows: 20 kg of polyethylene glycol dicarboxylic acid, 6 kg of 1-(3-hydroxypropyl)pyrrole, 2 kg of guaiacol, 6 kg of p-toluenesulfonic acid, and 300 kg of anhydrous toluene are weighed according to the mass ratio (kg). Step 1: Low-temperature esterification: 1-(3-hydroxypropyl)pyrrole is added at 80℃ and selectively esterified with one end of the carboxyl group of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate. Step 2: High-temperature esterification: Guaifenesin is added at 100℃ and esterified with the remaining carboxyl group to complete the double-end grafting. At this temperature, toluene and water azeotropically react to continuously remove reactive water, promoting complete esterification. Step 3: Purification treatment: The reaction endpoint is defined as a constant acid value and no reactive water precipitation. After neutralization, impurity removal, desolventization under reduced pressure, and vacuum drying, a double-end grafted modified composite esterification stabilizer is obtained.
[0082] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution was added dropwise to the alkaline alcohol-water system at a constant rate of 3.0 mL / min. The reaction was carried out in a closed reactor with a reaction pressure of 0.08 MPa. The total dropwise time was controlled to be 180 min. The reaction temperature was controlled to be 35 °C and the stirring speed was 900 rpm during the dropwise process. After the dropwise addition was completed, the reaction was continued at a constant temperature for 8 h. The total solid content of the reaction system was controlled to be 14 wt.% throughout the process. The two silicates underwent synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0083] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 9000 rpm for 15 min and the bottom solid precipitate was collected. It was washed 4 times with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 8 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0084] (5) Drying treatment: The washed wet product is placed in an 80℃ vacuum drying oven and dried under vacuum for 12 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0085] Comparative Example 1
[0086] (1) Preparation of alkaline alcohol-water reaction system: 65 kg of anhydrous ethanol, 12 kg of deionized water and 4 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 25 wt.%; the mixture was stirred at 400 rpm for 10 min at 20℃ to form a clear and homogeneous alkaline alcohol-water system.
[0087] (2) Preparation of composite silicate precursor solution: According to the mass kg, 18 kg of tetraethoxysilane and 1.5 kg of methyltriethoxysilane are mixed. The purity of tetraethoxysilane is ≥99 wt.% and the purity of methyltriethoxysilane is ≥98 wt.%. Then add 0.2 kg of dispersant stabilizer polyvinylpyrrolidone, stir at room temperature for 5 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0088] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a constant rate of 0.8 mL / min. The reaction is carried out in a closed reactor at atmospheric pressure. The total dropwise time is controlled at 40 min. The reaction temperature is controlled at 25 °C and the stirring speed is controlled at 500 rpm during the dropwise process. After the dropwise addition is completed, the reaction is continued at a constant temperature for 3 h. The total solid content of the reaction system is controlled at 6 wt.% throughout the process. The two silicates undergo synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0089] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 5000 rpm for 5 min and the bottom solid precipitate was collected. It was washed twice with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 4 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0090] (5) Drying treatment: The washed wet product is placed in a vacuum drying oven at 50°C and dried under vacuum for 6 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0091] Comparative Example 2
[0092] (1) Preparation of alkaline alcohol-water reaction system: 65 kg of anhydrous ethanol, 12 kg of deionized water and 4 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 25 wt.%; the mixture was stirred at 400 rpm for 10 min at 20℃ to form a clear and homogeneous alkaline alcohol-water system.
[0093] (2) Preparation of composite silicate precursor solution: According to the mass kg, 18 kg of tetraethoxysilane and 1.5 kg of methyltriethoxysilane are mixed. The purity of tetraethoxysilane is ≥99 wt.% and the purity of methyltriethoxysilane is ≥98 wt.%. Then add 0.2 kg of dispersant stabilizer, stir at room temperature for 5 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0094] The specific preparation process of the dispersion stabilizer is as follows: 10 kg of polyethylene glycol dicarboxylic acid, 0.3 kg of guaiacol, 3 kg of p-toluenesulfonic acid, and 200 kg of anhydrous toluene are weighed according to the mass ratio (kg). Step 1: Polyethylene glycol dicarboxylic acid is heated at 75°C. Step 2: High-temperature esterification: Guaifenesin is added at 90°C to complete the double-end grafting with the remaining carboxyl groups. At this temperature, toluene and water azeotropically carry out the reaction water, promoting complete esterification. Step 3: Purification treatment: The reaction endpoint is defined as a constant acid value and no precipitation of raw water. After neutralization to remove impurities, desolventization under reduced pressure, and vacuum drying, the dispersion stabilizer is obtained.
[0095] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a constant rate of 0.8 mL / min. The reaction is carried out in a closed reactor at atmospheric pressure. The total dropwise time is controlled at 40 min. The reaction temperature is controlled at 25 °C and the stirring speed is controlled at 500 rpm during the dropwise process. After the dropwise addition is completed, the reaction is continued at a constant temperature for 3 h. The total solid content of the reaction system is controlled at 6 wt.% throughout the process. The two silicates undergo synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0096] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 5000 rpm for 5 min and the bottom solid precipitate was collected. It was washed twice with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 4 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0097] (5) Drying treatment: The washed wet product is placed in a vacuum drying oven at 50°C and dried under vacuum for 6 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0098] Comparative Example 3
[0099] (1) Preparation of alkaline alcohol-water reaction system: 65 kg of anhydrous ethanol, 12 kg of deionized water and 4 kg of ammonia water were added to a closed reactor by mass kg; wherein the purity of anhydrous ethanol was ≥99.5 wt.%, the conductivity of deionized water was ≤1 μS / cm and the concentration of ammonia water was 25 wt.%; the mixture was stirred at 400 rpm for 10 min at 20℃ to form a clear and homogeneous alkaline alcohol-water system.
[0100] (2) Preparation of composite silicate precursor solution: According to the mass kg, 18 kg of tetraethoxysilane and 1.5 kg of methyltriethoxysilane are mixed. The purity of tetraethoxysilane is ≥99 wt.% and the purity of methyltriethoxysilane is ≥98 wt.%. Then add 0.2 kg of dispersant stabilizer, stir at room temperature for 5 min, and after mixing evenly, a clear composite silicate precursor solution is obtained.
[0101] The specific preparation process of the dispersion stabilizer is as follows: Weigh 10 kg of polyethylene glycol dicarboxylic acid, 2 kg of 1-(3-hydroxypropyl)pyrrole, 3 kg of p-toluenesulfonic acid, and 200 kg of anhydrous toluene according to the mass ratio (kg); Step 1, low-temperature esterification: Add 1-(3-hydroxypropyl)pyrrole at 75℃ and selectively esterify it with the carboxyl group at one end of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate; Step 2, high-temperature esterification: Raise the temperature to 90℃, at which temperature toluene and water azeotropically react to continuously remove the reaction water and promote complete esterification; Step 3, purification treatment: Use a constant acid value and no precipitation of water as the reaction endpoint, neutralize and remove impurities, desolventize under reduced pressure, and vacuum dry to obtain the dispersion stabilizer.
[0102] (3) Synergistic hydrolysis and polycondensation reaction: The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a constant rate of 0.8 mL / min. The reaction is carried out in a closed reactor at atmospheric pressure. The total dropwise time is controlled at 40 min. The reaction temperature is controlled at 25 °C and the stirring speed is controlled at 500 rpm during the dropwise process. After the dropwise addition is completed, the reaction is continued at a constant temperature for 3 h. The total solid content of the reaction system is controlled at 6 wt.% throughout the process. The two silicates undergo synergistic hydrolysis and polycondensation reaction to generate submicron-sized spherical silica slurry with uniform particle size.
[0103] (4) Solid-liquid separation and washing: The obtained silica slurry was centrifuged at 5000 rpm for 5 min and the bottom solid precipitate was collected. It was washed twice with anhydrous ethanol and deionized water, with the amount of washing liquid added each time being 4 times the mass of the precipitate, to fully wash away residual ammonia, alcohol solvents and unreacted silicate monomers.
[0104] (5) Drying treatment: The washed wet product is placed in a vacuum drying oven at 50°C and dried under vacuum for 6 hours to completely remove residual solvent and moisture, and finally obtain submicron-sized uniform spherical silica powder.
[0105] Test method:
[0106] 1. Particle size and particle size distribution test
[0107] The average particle size and particle size distribution index (PDI) were measured using a Zetasizer Nano ZS90 dynamic light scattering particle size analyzer (DLS) from Malvern, UK.
[0108] Test conditions:
[0109] Dispersion medium: anhydrous ethanol;
[0110] Dispersible concentration: 0.05 wt.%;
[0111] Ultrasonic dispersion time: 10 min;
[0112] Test temperature: 25℃;
[0113] Each group of samples was tested in parallel three times and the average value was taken.
[0114] in:
[0115] The average particle size is represented by the Z-average value;
[0116] PDI value is used to evaluate particle size uniformity;
[0117] Particles with a PDI ≤ 0.08 are considered to have high homogeneity.
[0118] 2. Scanning Electron Microscopy (SEM) Testing
[0119] The particle morphology, sphericity, and aggregation were observed using a Hitachi SU8010 field emission scanning electron microscope (SEM) from Japan.
[0120] Test conditions:
[0121] Accelerating voltage: 5 kV;
[0122] Gold spraying time: 40 seconds;
[0123] Magnification: 50,000x.
[0124] Sphericity calculation:
[0125] 100 particles were randomly selected, and their roundness was calculated using image analysis software.
[0126] Circularity = 4πA / P 2
[0127] in:
[0128] A represents the projected area of the particle;
[0129] P is the particle perimeter.
[0130] The closer the roundness is to 1, the higher the sphericity.
[0131] 3. Specific surface area test
[0132] BET tests were performed using a Micromeritics ASAP 2460 fully automated surface area analyzer.
[0133] Test conditions:
[0134] Degassing temperature: 180℃;
[0135] Degassing time: 6 hours;
[0136] Adsorbed gas: N2;
[0137] Test temperature: 77 K.
[0138] 4. Tap density test
[0139] The density was measured using a powder tap density tester.
[0140] Test conditions:
[0141] Vibration frequency: 250 times / min;
[0142] Vibration frequency: 3000 times.
[0143] A higher tap density indicates better particle sphericity and packing performance.
[0144] Table 1 Test Results
[0145] Average particle size (nm) PDI Circularity <![CDATA[BET specific surface area (m 2 / g)]]> <![CDATA[Tap density (g / cm 3 )]]> Example 1 512 0.072 0.91 84.6 0.72 Example 2 326 0.066 0.94 86.1 0.75 Example 3 684 0.061 0.95 86.8 0.77 Example 4 445 0.053 0.97 87.4 0.78 Comparative Example 1 551 0.121 0.88 80.2 0.68 Comparative Example 2 534 0.104 0.90 82.5 0.70 Comparative Example 3 480 0.093 0.90 83.0 0.71
[0146] As can be seen from the performance comparison data table, the novel modified monomers synthesized by esterification of ethylene glycol dicarboxylic acid, 1-(3-hydroxypropyl)pyrrole, and guaiacol, combined with the synergistic hydrolysis process of dual silicates, show significant improvements in particle size uniformity, sphericity, specific surface area, and powder compaction and packing performance compared to the control examples using a single silicon source. This invention effectively solves the shortcomings of the traditional Stöber method, such as wide particle size distribution, poor sphericity, and easy particle agglomeration, through the structural design of the novel esterification stabilizer monomer and the compounding and control of the composite silicon source. The samples in each example exhibit regular overall morphology, good dispersibility, and excellent packing performance. The process can stably prepare high-quality submicron-sized spherical silica, demonstrating significant comprehensive performance advantages compared to traditional preparation routes and substantial industrial application value.
[0147] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing submicron-sized uniformly sized spherical silica via synergistic hydrolysis of silica esters, characterized in that, Includes the following steps: (1) Preparation of alkaline alcohol-water reaction system: According to the mass fraction, 65-78 parts of anhydrous ethanol, 12-20 parts of deionized water and 4-8 parts of ammonia water are added to the reactor and stirred at 400-700 rpm for 10-25 minutes at 20-30℃ to form a homogeneous alkaline alcohol-water system. (2) Preparation of composite silicate precursor solution: According to the mass fraction, 18-28 parts of tetraethoxysilane and 1.5-4.5 parts of methyltriethoxysilane are mixed, and then 0.2-1.2 parts of dispersant stabilizer are added. The mixture is stirred at room temperature for 5-20 minutes to obtain a composite silicate precursor solution. (3) Synergistic hydrolysis and condensation reaction: The composite silicate precursor solution is added dropwise to the alkaline alcohol-water system at a rate of 0.8–3.0 mL / min. During the dropwise addition, the reaction temperature is controlled at 25–35 °C and the stirring speed is controlled at 500–900 rpm. After the dropwise addition is completed, the reaction continues for 3–8 h to allow the silicate to undergo synergistic hydrolysis and condensation reaction to generate submicron-sized spherical silica slurry. (4) Solid-liquid separation and washing: The obtained slurry was centrifuged at 5000-9000 rpm for 5-15 min, the precipitate was collected, and washed 2-4 times alternately with anhydrous ethanol and deionized water, with the amount of washing solution added each time being 4-8 times the mass of the precipitate. (5) Drying treatment: The washed product was dried under vacuum at 50–80°C for 6–12 h to obtain submicron-sized uniform spherical silica powder. The dispersion stabilizer is prepared by reacting polyethylene glycol dicarboxylic acid, 1-(3-hydroxypropyl)pyrrole, 0.3-2 parts of guaiacol, and p-toluenesulfonic acid.
2. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: The anhydrous ethanol has a purity ≥ 99.5 wt.%; the deionized water has a conductivity ≤ 1 μS / cm.
3. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: The ammonia concentration is 25–28 wt.%.
4. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: The tetraethoxysilane has a purity ≥99 wt.% and its chemical formula is Si(OC2H5)4; the methyltriethoxysilane has a purity ≥98 wt.% and its chemical formula is CH3Si(OC2H5)3.
5. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: The dispersion stabilizer is prepared by dissolving polyethylene glycol dicarboxylic acid in anhydrous toluene, adding p-toluenesulfonic acid to construct an anhydrous homogeneous system, and then using a three-step process. The specific preparation steps are as follows: According to the mass ratio: weigh 10-20 parts of polyethylene glycol dicarboxylic acid, 2-6 parts of 1-(3-hydroxypropyl)pyrrole, 0.3-2 parts of guaiacol, 3-6 parts of p-toluenesulfonic acid, and 200-300 parts of anhydrous toluene; Step 1, Low-temperature esterification: 1-(3-hydroxypropyl)pyrrole is added at 75-80℃ and selectively esterified with the carboxyl group at one end of polyethylene glycol dicarboxylic acid to prepare a monopyrrole ester intermediate; Step 2, high-temperature esterification: The temperature is raised to 90-100℃ and guaiacol is added to complete the double-end grafting with the remaining carboxyl groups; at this temperature, toluene and water azeotropically carry out the reaction water, promoting the complete esterification. The third step is purification: the reaction ends when the acid value of the system is constant and no water is precipitated. After neutralization and impurity removal, desolventization under reduced pressure and vacuum drying, a double-end grafted modified composite esterification stabilizer is obtained.
6. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: In step (3), the material is added by constant-rate dripping, and the dripping time is controlled to be 40-180 min.
7. The method for preparing submicron-sized uniformly sized spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: In step (3), the synergistic hydrolysis reaction is carried out in a closed reactor at a pressure ranging from atmospheric pressure to 0.08 MPa.
8. The method for preparing submicron-sized uniform spherical silica by synergistic hydrolysis of silicate esters according to claim 1, characterized in that: In step (3), the total solid content of the reaction system is controlled to be 6-14 wt.%.
